A STUDY OF CORRELATION BETWEEN AGENT, HOST, ENVIRONMENT AND VACCINE FACTORS WITH PREVALENCE OF RABIES IN INDONESIA 2015 - Setyowati, Tyas Ika Budi; Machmud, Putri Bungsu (Indonesian Journal of Tropical and Infectious Disease, 2018)
A zoonotic disease has been global threat related to health and one of them is rabies. More than 150 countries around the world has infected by rabies disease problem and the case fatality rate (CFR) reaches 100%, which there are 55,000 people died every year because of rabies. In Indonesia, there are 25 from 34 province, which has endemic of rabies disease. The purpose of this study is to know the correlation between the factors of the agent, host, and environment and also anti rabies vaccine with the prevalence of rabies in Indonesia at 2015. The study used correlation design which using Indonesian zoonotic reported data by Ministry of Health and also used other secondary data, which is provided by central bureau of statistic Indonesia (BPS).  The provinces that included in this study are the endemic provinces associated with the rabies incident that reported to Ministry of Health and have the completeness of data in 2015. A total of 22 provinces was included in this study, which only use Rabies cases from dog's bite only. Rabies that source from others animal's bite could not included in this study because of data limitations. This study used simple linear of regression statistical tests through provincial as unit analysis. The result of this study showed that there were correlations between agent that have positive specimens (r=0.606, P value =0.0003), status of working participation rate (r=0.435, P value 0.004) and also coverage of rabies vaccine (r=-0.567, P value =0.041) with the prevalence of rabies disease. In summary, there are a positive correlation between positive specimen of agent and also status of working participant rate with the prevalence of rabies disease. However, rabies vaccine coverage has negative correlation. Furthermore, there is no correlation between environment factors and prevalence of rabies disease in this study. It still need further research to be more research on a smaller level with variables that varied.